Diversidade genética de Brycon orbignyanus em sistema reprodutivo seminatural - Lopera Barrero, Nelson Mauricio (2007)
Several ecological and climatic factors and especially those related to man's actions have led to the disappearance of piracanjuba (Brycon orbignyanus) natural populations. For the importance of the ecosystems in which it is located and by its qualities of fast growth and good adaptation to controlled environments, in the last years the producer's interest in the use of such migratory species has increased, aiming the production and the participation in conservation and stock enhancement programs. In the implementation of management and stock enhancement programs as conservation strategies, the genetic monitoring, the evaluation of reproductive procedures and the scientific support of different areas are necessary to obtain a correct maintenance and a greater objectivity of such programs. The purpose of this study was to evaluate the influence of the reproductive and semi-natural systems in the genetic diversity and the parental contribution of B. orbignyanus offspring's destined to stock enhancement programs of the Paranapanema River with the RAPD (Random Amplified Polymorphic DNA) and microsatellites molecular markers. The results showed an increase of the genetic variability when an equal proportion of sex was used, possibly due to the effective broodstock number used in the mating and the semi-natural reproductive system. The semi-natural system allowed the preservation of the reproducers in the reproductive process. The occurrence of multiple paternities and the reproductive dominance was verified. These results provide information's that will contribute to the development of management models in B. orbignyanus, ensuring a correct genetic and a reproductive monitoring that are important for a safe conservation of the specie.